Extending the shelf life of tomato through hurdle technology – a review - Nassarawa, Shamsudeen Sanusi; Sulaiman, Salamatu Ahamad; Bako, Hadiza Kabir; Shehu, Amina Muhammad; Dandago, Munnir Abba (Journal of Postharvest Technology, 2019)
This paper is a review on little history of tomatoes, nutritional profile of tomatoes, health benefit, hurdle technology, application of hurdle technology and Hurdle technology in the postharvest preservation of fresh tomatoes. Furthermore, the paper explains the various ways the principles of hurdle technology can be applied in the preservation of the freshness and quality of fruits and vegetables considering tomato as a case study. In order to reduce the postharvest loss of this commodity, various researches have been carried out on the best methods to employ. These techniques are aimed at extending shelf life and preserving the freshness and quality of the product from the time of harvest to final consumption. Technologies such as Controlled Atmosphere Storage (CAS), passive and active Modified Atmosphere Packaging (MAP), cold storage, waxing, and chlorine treatment, have been employed all in a bid to extend postharvest shelf life and quality. Some of these techniques are used individually or combined.